Identifikasi Faktor yang Mempengaruhi Pemilihan Rumah oleh Aparatur Sipil Negara Dinas Kesehatan dan Dinas Pariwisata – Kebudayaan Kabupaten Magelang - Fahmi F. Alrizal; Siti Choiriyah; M. Ferdaus Noor A; Dewi Puspitasari (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2019)
Home needs by humans for shelter, gathering, family activities as well as investment goods are very necessary. However, in the process of home ownership many criteria are determined, especially in terms of income. Even those who have fixed income such as Civil Servant are not necessarily easy to choose and own their own homes. Many factors must be considered such as internal and external factors in choosing a house that will affect home ownership. To find out what factors are affecting in the decision to choose home using statistical analysis with a case study at the civil servant in Departement of Health and the Tourism-Culture of Magelang District. Based on statistical analysis, the results of the variable validity and reliability test meet the requirements. Then through testing the normality of normal distribution data. Looking for equations with multiple linear regression then hypotesis in the t test shows that internal and external variables together influence the decision to choose a house. While the f test shows a significance of 0.05, this means that the internal and external variables together have a positive effect on the decision to choose a house. Whereas the factors that are affecting in choosing a house are functional and effective house plans.